PENGARUH PENGGUNAAN MEDIA INTERNET TERHADAP MINAT BELAJAR SEJARAH KEBUDAYAAN ISLAM SISWA KELAS X MADRASAH ALIYAH DARUL FALAH CUKIR JOMBANG TAHUN PELAJARAN 2017-2018: PENGARUH PENGGUNAAN MEDIA INTERNET TERHADAP MINAT BELAJAR SEJARAH KEBUDAYAAN ISLAM SISWA KELAS X MADRASAH ALIYAH DARUL FALAH CUKIR JOMBANG TAHUN PELAJARAN 2017-2018 - Purwanti, Sholihul Anshori (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article examines the Effect of the Use of Internet Media on Interest in Learning theHistory of Islamic Culture Class X Madrasah Aliyah Darul Falah Cukir Jombang Academic Year2017-2018. With a quantitative approach to the test of influence, this study produced findings thatthe application of internet usage in SKI lessons was proven to increase student interest in learning.It can be seen from the percentage of questionnaires that have been distributed to 20 students ineach class. Based on the percentage of high category interest in the experimental class by 85%more than the percentage of high interest category in the control class that is 50%. In the analysisof mann witney it is read and explained Asymp. Sig. (2-tailed) interest = 0.002 which proves thatthere is a significant influence on the use of internet media on student learning interests. Theinfluence can be seen from the difference between the interests of the experimental class that is theclass treated using internet media, higher than the interest of the control class that is the class thatis not treated and the mean rank of the experimental class 26.30 is higher than the mean rank of14.70.Keywords: Media, Internet, Interest in Learning